2008
DOI: 10.1111/j.1750-3841.2008.00899.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antibacterial Activity of Whey Protein Isolate Coating Incorporated with Nisin, Grape Seed Extract, Malic Acid, and EDTA on a Turkey Frankfurter System

Abstract: The effectiveness of whey protein isolate (WPI) coatings incorporated with grape seed extract (GSE), nisin (N), malic acid (MA), and ethylenediamine tetraacetic acid (EDTA) and their combinations to inhibit the growth of Listeria monocytogenes, E. coli O157:H7, and Salmonella typhimurium were evaluated in a turkey frankfurter system through surface inoculation (approximately 10(6) CFU/g) of pathogens. The inoculated frankfurters were dipped into WPI film forming solutions both with and without the addition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(82 citation statements)
references
References 29 publications
1
80
0
1
Order By: Relevance
“…Like other natural antimicrobials, GSE is not reported to exhibit toxicity or adverse health effects at the dose of 50 to 100 mg per day (16,36,38,42,43,49). GSE is known to be nonmutagenic, nonclastogenic, and nonaneugenic (49).…”
mentioning
confidence: 99%
“…Like other natural antimicrobials, GSE is not reported to exhibit toxicity or adverse health effects at the dose of 50 to 100 mg per day (16,36,38,42,43,49). GSE is known to be nonmutagenic, nonclastogenic, and nonaneugenic (49).…”
mentioning
confidence: 99%
“…Similarly, a previous study demonstrated that extracts and fractions of green tea had bacteriostatic activity against some vibrio species (Toda et al, 1989). Also, multiple lethality hurdles to the growth of pathogens including Listeria monocytogenes, Escherichia coli and Salmonella typhimurium can be provided by using lesser amount of chemical antimicrobials in combination with natural antimicrobials from green tea and grape seed extracts (Gadang et al, 2008;Chanet al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study, the liquid extracts of green tea seedhave shown inhibitory effects on some Grampositive as well as Gram-negative bacteria (Gadang et al, 2008). No Vibriospecies were tested in this study.On the other hand, the green tea extract had a weak/medium activity against Vibrio cholera (Hamilton-Miller, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial nanoparticles that have been synthesized and tested for applications in antimicrobial packaging and food storage boxes include silver oxide nanoparticles (Sondi and Salopek-Sondi 2004), zinc oxide, and magnesium oxide nanoparticles ) and nisin particles produced from the fermenation of a bacteria (Gadang et al 2008).…”
Section: Antimicrobial Packagingmentioning
confidence: 99%